Consumers' perceived security risks in online shopping: a survey study in sri lanka - Ilmudeen, A. (university of Jaffna, 2014)
Consumers' perceived security risks in online shopping is an important aspects which influence consumer's buying behavior in online. This paper focuses ten dimensions of consumer perceived risk such as performance risk, physical risk, financial risk, sauce risk, security risk, delivery risk, time risk, social risk, psychological risk and privacy risk in Sri Lankan context. Research question and hypotheses were determined after the wide spectrum of literature review. Structured questionnaire method used to collect the data and there were 128 respondent participated in this research study. The results also proved that privacy and security concerns are the main barriers to shopping on the Internet. The analysis include descriptive analysis, the Pearson correlation analysis and t-test. From this research study it can be concluded that, the column " importance" the hypotheses such as financial risk, delivery risk, time risk, social risk, psychological risk and privacy risk has negative effect on attitudes towards online shopping. On the other hand the column "the chance the risk occur" the hypotheses such as performance risk, physical risk, financial risk, sauce risk, security risk, delivery risk, time risk, social risk, psychological risk and psychological risk has negative effective on attitudes towards online shopping.
Keywords: Security; Risk; Online shopping; Risk dimension